Analysis of Implementation Standards of Sharia Minimum Services in the Hospital: Case Study at Sari Asih Sangiang Hospital 2018 - Mardiyati, Fitri Yuli; Ayuningtyas, Dumilah (UI Scholars Hub, 2021)
The development of sharia-based hospitals in Indonesia began with the Indonesian Islamic Health Effort Assembly (MUKISI) in collaboration with the National Sharia Council of the Indonesian Ulema Council (DSN-MUI) with the issuance of fatwa No. 107 / DSN-MUI / X / 2016 concerning Guidelines for Implementing Hospitals Based on Sharia Principles. One of them is Sari Asih Sangiang Hospital (RSSA) in the city of Tangerang, which has received sharia certification since 2018. Sharia hospitals guideline regulates Sharia Minimal Service Standards (SPM). The SPM contains regulations of reciting basmalah before procedures, hijab for patients and breastfeeding mother, mandatory training for patient's fiqh, Islamic education, gender-based ECG usage, using of hijab in the operating room, and scheduling elective surgery which not constrained by prayer times. This study uses a qualitative approach through report document review on the implementation of sharia quality indicators. The indicator format is determined by checklist, survey, medical record document; daily, monthly, and annual census recapitulation; secondary data from previous research, related literature, and in-depth interviews with correspondent criteria who responsible for implementing Sharia Quality at Sari Asih Sangiang Hospital. The results show that Sari Asih Sangiang Hospital has implemented Sharia SPM optimally, whose implementation refers to the standards and guidelines for the implementation of sharia hospitals issued by the DSN-MUI but is still constrained with the data recording problem. We suggest to put forward the need for coaching and training in Human Resources, and data recording should be done more regularly in order to maximize achievement targets.